2017
DOI: 10.1007/s11682-017-9772-1
|View full text |Cite
|
Sign up to set email alerts
|

Parsing the neural correlates of anxious apprehension and anxious arousal in the grey-matter of healthy youth

Abstract: Neuroscientific and psychological research posits that there are two transdiagnostic facets of anxiety: anxious arousal and anxious apprehension. Though these two facets of anxiety are distinct, they are often subsumed into one domain (e.g., trait anxiety). The primary goal of the current study was to delineate the relationship between anxious arousal and cortical thickness versus the relationship between anxious apprehension and cortical thickness in a sample of typically functioning youth. The secondary aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 102 publications
0
7
3
Order By: Relevance
“…Additionally, previous research identified regions outside of the PFC that may influence emotion, emotion regulation, and related traits, such as anxiety. These regions include the thalamus, hippocampus, insula, and midbrain (Castagna et al, 2018;Silvers et al, 2017), areas that we did not examine in the present study. A logical avenue for future research would be to work towards understanding the direction, or directions, of influence in this circuit and how connections with other regions of the brain may affect amygdala function perhaps utilizing an effective functional connectivity analysis approach.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research identified regions outside of the PFC that may influence emotion, emotion regulation, and related traits, such as anxiety. These regions include the thalamus, hippocampus, insula, and midbrain (Castagna et al, 2018;Silvers et al, 2017), areas that we did not examine in the present study. A logical avenue for future research would be to work towards understanding the direction, or directions, of influence in this circuit and how connections with other regions of the brain may affect amygdala function perhaps utilizing an effective functional connectivity analysis approach.…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric characteristics of the measures chosen may have impacted results. In the examination of anxiety, it is often valuable to distinguish between anxious arousal (physiological symptoms such as increased heartbeat, sweating) and anxious apprehension (verbal rumination, worry; Castagna et al, 2018;Nitschke, Heller, Palmieri, & Miller, 1999). The GAD-7, used in this study, is correlated with measures that clearly distinguish between the two types of anxiety, such as the Beck Anxiety Inventory (BAI, r=.70), the Depression, Anxiety, and Stress Scales -Anxious Arousal subscale (DASS-A, r=.71), and the Penn State Worry Questionnaire (PSWQ, r=.76;Rutter & Brown, 2017;Seo & Park, 2015;Spitzer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the anxious-arousal-specific factor would be associated with gray-matter morphometry of regions supporting threat processing (i.e., the amygdala; Öhman, 2005) and sensorimotor regions involved with the physiological responses to threat. Finally, we predicted that the anxious-apprehension-specific factor would be associated with left-lateralized prefrontal regions associated with verbalizations of worry (Engels et al, 2007; Nitschke et al, 1999; Sharp et al, 2015) and the hippocampus given previous associations of anxious apprehension but not anxious arousal in children (Castagna et al, 2018).…”
mentioning
confidence: 99%
“…In the current study, we employed a bifactor model of internalizing symptoms to identify brain regions associated with four internalizing dimensions: a common internalizing dimension capturing symptoms that are shared across depression and anxiety and three specific symptom dimensions, including a low-positive-affect-specific dimension, an anxious-arousal-specific dimension, and an anxious-apprehension-specific dimension. Although a handful of studies have investigated the neuroanatomical correlates of related dimensions (e.g., Cardinale et al, 2019; Castagna et al, 2018; Holmes et al, 2012; Lener et al, 2016), to our knowledge, no study has employed bifactor modeling to parse common and unique variance between the four internalizing symptom dimensions. We used a bifactor-model approach because it allowed us to differentiate between common and specific symptom dimensions, something that alternative parameterizations are unable to do (Bornovalova et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation